Malaria infection and the anthropological evolution Infecção por Malária e evolução antropológica - Sergio Sabbatani; Roberto Manfredi; Sirio Fiorino (Universidade de São Paulo, 2010)
During the evolution of the genus Homo, with regard to species habilis, erectus and sapiens, malaria infection played a key biological role, influencing the anthropological development too. Plasmodia causing malaria developed two kinds of evolution, according to a biological and philogenetical point of view. In particular, Plasmodium vivax, Plasmodium malariae, and Plasmodium ovale, would have either coevolved with human mankind (coevolution), or reached human species during the most ancient phases of genus Homo evolution. On the other hand, Plasmodium falciparum has been transmitted to humans by monkeys in a more recent period, probably between the end of Mesolithic and the beginning of Neolithic age. The authors show both direct and indirect biomolecular evidences of malaria infection, detected in buried subjects, dating to the Ancient World, and brought to light in the course of archeological excavations in some relevant Mediterranean sites. In this literature review the Authors organize present scientific evidences: these confirm the malarial role in affecting the evolution of populations in Mediterranean countries. The people living in several different regions on the Mediterranean Sea sides, the cradle of western civilization, have been progressively influenced by malaria, in the course of the spread of this endemic disease during the last millennia. In addition, populations affected by endemic malaria developed cultural, dietary and behaviour adaptations, contributing to decrease the risk of disease. These habits were not probably fully conscious. Nevertheless it may be thought that both these customs and biological modifications, caused by malarial plasmodia, favoured the emergence of groups of people with a greater resistance against malaria. All these considered factors decreased demographical impact, influencing in a favourable way the general development and growth of civilization. Durante a evolução do gênero Homo a infecção por malária exerceu papel biológico chave, influenciando até o desenvolvimento antropológico. Os Plasmódios causadores da malária desenvolveram dois tipos de evolução, segundo um ponto de vista biológico, e filogenético. Em particular, os Plasmódios vivax, malariae, e ovale poderiam ter coevoluído com a espécie humana ou ter atingido esta durante as fases mais antigas da evolução do gênero HOMO. Por outro lado, o Plasmódio falciparum teria sido transmitido aos humanos por macacos num período mais recente, provavelmente entre o fim da Idade Mesolítica e o início da Neolítica. Os Autores mostram evidências biomoleculares, tanto diretas como indiretas, de infecção por malária, observada em indivíduos enterrados, reportando ao Mundo Antigo, e trazidas à luz no decorrer de escavações arqueológicas em alguns sítios relevantes Mediterrâneos. Nesta revisão da literatura, os autores organizam evidências modernas. Confirmam o papel da malária ao afetar a evolução das populações no Mediterrâneo. As pessoas que moram nas várias regiões do Mediterrâneo foram progressivamente influenciadas pela malária, ao longo do avanço desta doença. Além disso, as populações afetadas desenvolveram adaptações culturais, alimentares, e de comportamento, contribuindo para uma redução no risco da doença. Entretanto, pode ser que ambas modificações (as biológicas e as dos hábitos) usadas pelos Plasmódios da malária, favoreceram a emergência de grupos de pessoas com maior resistência contra a malária. Todos estes fatores considerados reduziram o impacto demográfico, influenciando de uma maneira favorável o desenvolvimento em geral, e o crescimento da civilização.